Clinical diagnostic value of liquid chromatography-tandem mass spectrometry method for primary aldosteronism in patients with hypertension: A systematic review and meta-analysis - Hua, Kai-Fang; Wu, Yan-Hui; Zhang, Shi-Ting (Frontiers in Endocrinology, 2022)
Background. Primary aldosteronism (PA) is currently considered the most common cause of secondary and endocrine hypertension. Liquid chromatography-tandem mass spectrometry (LC-MS/MS) as a new detection technique has been gradually applied in the diagnosis of PA. However, the diagnostic value of LC-MS/MS methods for PA has not been systematically clinically validated. The aim was to access the diagnostic accuracy, sensitivity, and specificity of LC-MS/MS methods as screening tools in PA. Materials and methods. A literature search of PubMed, Embase, Medline, Web of Science, Scopus, Science Direct, and Chinese databases was carried out to June 2022 with no language restriction. Data on sensitivity and specificity and other evaluation indicators were extracted and pooled with STATA and Meta-disc software. Heterogeneity was evaluated and meta-regression and subgroup analysis was performed to elucidate sources of heterogeneity. Results.12 studies of the diagnostic test were suitable and included in the meta-analysis. Pooled sensitivity, specificity, and diagnostic odds ratio were 0.89 (95% CI: 0.83-0.93), 0.87 (95% CI: 0.82-0.91), and 55 (95% CI: 28-110), respectively. Subgroup analysis assessed the diagnostic power of LC-MS/MS based on the type of detection index. ARR and PAC based on LC-MS/MS methods have the higher diagnostic value compared with other indices, diagnostic odds ratios were 121.65 (95% CI: 36.28-407.98) and 49.85 (95% CI: 24.87-99.93). There was considerable heterogeneity among studies. Conclusion. LC-MS/MS methods had higher accuracy and reliability in the diagnosis of primary aldosteronism. LC-MS/MS-based ARR and PAC can be further promoted and applied in the diagnosis of primary aldosteronism. Keywords: meta-analysis; aldosterone; primary aldosteronism; LC-MS/MS; diagnostic test;